Leader-organization fit: comparing the effectiveness of paternalistic and transformational leadership in different organizational cultures - Duarte, Lucas Farias Zarconi Cavalcanti (2014)
Research on paternalistic leadership (PL) has been based exclusively on national cultures´ differences. However there are cues that other contextual variables can add to the explanation of this construct. Due to its capacity to influence expectations of individuals in organizations, organizational culture can contribute to fill this gap. To test if organizational culture influences the effectiveness of leadership style, we conducted two experimental studies using Amazon’s Mechanical Turk, comparing effects of paternalistic and transformational leadership on followers’ outcomes. Using video clips and vignettes, we found that PL is better related to followers´ outcomes in cultures oriented to people than outcome, and that TL has a better relationship in cultures oriented to innovation than stability. The results suggest that organizational culture helps in explaining PL endorsement, and that further analysis of the influence of this variable to PL can provide a better understanding of the expression of this leadership style in organizations.